Novelty 3D processing maps of GH4175 superalloy to predict the instability deformation and optimal processing parameters - Yueqian Li; Jiao Luo; Zhigang Zhang; Hong Li (Journal of Materials Research and Technology)
In this paper, a novel 3D processing map is developed by the three-dimensional cubic spline interpolation method. This 3D processing map is capable of reflecting the continuous variation of the efficiency of power dissipation and instability parameter as the processing parameters change. It is used to predict the instability deformation and optimal processing parameters during the hot deformation of GH4175 superalloy. The results indicate that the instability deformation is mainly contributed to the adiabatic shear band (ASB) and flow localization. The average grain size inside ASB, in transition region and outside ASB is ∼200 nm, ∼1 μm and ∼2 μm, respectively. The grain refinement of GH4175 superalloy inside ASB is motivated by Rotational Dynamic Recrystallization (RDR) and is also further accelerated by Discontinuous Dynamic Recrystallization (DDRX) and Hetero-epitaxial Recrystallization(HERX). Based on the prediction of 3D processing map, the deformation temperature ranging from 1052 °C to 1100 °C, the strain rates ranging from 0.001 s−1 to 0.067 s−1 and the strains ranging from 0.1 to 0.69 are chosen as the optimum processing parameters during isothermal compression of GH4175 superalloy. A perfect superplastic behavior with a high elongation of over 260 % for GH4175 superalloy is verified at this region.